PENGARUH LATIHAN OPERAN LARI MENYILANG TERHADAP KEMAMPUAN CHEST PASS BOLA BASKET TIM PUTRA SANJAYA BASKETBALL CLUB PEKANBARU - Martha Dinata; Slamet Slamet; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the effect of cross-running operand training on the chest pass ability of the Putra Sanjaya Basketball Club Pekanbaru Team. This research was conducted at the basketball court Sanjaya club Pekanbaru, Jalan Soekarno Hatta No. 11 Pekanbaru. Held from March 2020 to September 2020, and the number of samples was 12 people. Based on the analysis of observations in the field, it is known that there are still deficiencies that occur in the men's basketball team Sanjaya Basketball Club Pekanbaru, for example the passing is still inflated and not right towards the chest, before the analysis is carried out, first a pre-test is performed with an average result of 24.67, then carried out cross-run pass exercises for 16 meetings at the Putra Sanjaya Basketball Club Pekanbaru Basketball Team with a total of 12 people and obtained an average post-test result of 27.5. Based on the statistical t-test analysis, the difference value is 2.83 and results in tcount of 5.77 and t table of 1.79. Means tcount> ttable. It can be concluded that the Cross Running Operant (X) exercise has a significant effect on the Chest Pass Ability (Y) of the Sanjaya Basketball Club Pekanbaru Men's Basketball Team.Key Words: Cross Run Pass, Chest Passing Ability